2020
DOI: 10.21203/rs.3.rs-31723/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased pretreatment C-reactive protein-to-albumin ratio predicts severe coronavirus disease 2019

Abstract: Objective The aim of this study was to identify early warning signs for severe coronavirus disease 2019 (COVID-19). Methods We retrospectively analysed the clinical data of 90 patients with COVID-19 from Guanggu District of Hubei Women and Children Medical and Healthcare Center, comprising 60 mild cases and 30 severe cases. The demographic data, underlying diseases, clinical manifestations and laboratory blood test results were compared between the two groups. The cutoff values were determined by receiver oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This study concluded the superiority of hsCAR, hsCPAR, and PNI. PNI was superior to NLR in predicting mortality and CAR in predicting disease severity, each in one study (79,82).…”
Section: Nlr In Comparison With Other Markersmentioning
confidence: 95%
See 1 more Smart Citation
“…This study concluded the superiority of hsCAR, hsCPAR, and PNI. PNI was superior to NLR in predicting mortality and CAR in predicting disease severity, each in one study (79,82).…”
Section: Nlr In Comparison With Other Markersmentioning
confidence: 95%
“…CAR could predict disease severity in two studies (79,91): one comparing it with NLR and finding a higher OR for CAR (OR = 17.652, p = 0.001) than NLR (OR = 1.512, p = 0.007) (79).…”
Section: C-reactive Protein To Albumin Ratio and C-reactive Protein To Prealbumin Ratiomentioning
confidence: 99%
“…Human serum albumin level (HSAL) widely used in clinical practice, it reflects nutritional status and inflammatory response, which are related to outcomes of cancer treatment, and inflammatory diseases. Previous studies also found that HSAL was significantly lower in patients with severe COVID-19 (10).…”
Section: Introductionmentioning
confidence: 68%
“…After exclusions, 23 studies with a total of 7774 participants remained and were ultimately included in the analysis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 The process of study selection is summarised in Supplementary Figure 1 using the PRISMAflowchart. Sixteen studies reported the association of CAR with COVID‐19 outcomes, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 four studies included FAR, 28 , 29 , 30 , 31 and three studies included both CAR and FAR.…”
Section: Resultsmentioning
confidence: 99%